The Effects of Trade Liberalization on Groundnut Market in Myanmar - Nyein, Khin Myo; Sirisupluxana, Prapinwadee; Titapiwatanakun, Boonjit (Asian Journal of Applied Economics, 2013)
บทคัดย่อ สินค้าถั่วลิสงมีส่วนแบ่งตลาดภายในประเทศสูง และมีบทบาทสำคัญต่อการความเป็นอยู่ของเกษตรกร ผู้แปรรูป และผู้บริโภค อย่างไรก็ตามรัฐบาลพม่าได้มีการแทรกแซงตลาดพืชน้ำมันและผลิตภัณฑ์ผ่านนโยบายเกษตรและการค้า โดยห้ามส่งออกเมล็ดถั่วลิสงแม้ว่าสินค้านี้มีความสามารถในการแข่งขันในตลาดต่างประเทศก็ตาม ทั้งนี้เพื่อรักษาปริมาณให้เพียงพอต่อความต้องการใช้น้ำมันพืชภายในประเทศ การเปิดตลาดถั่วลิสงน่าจะทำให้เกษตรกรและผู้แปรรูปได้รับประโยชน์ภายใต้การพิจารณาหลายๆ สถานการณ์ตลาด การศึกษานี้วิเคราะห์ถึงผลกระทบหากจะมีการค้าเสรีของถั่วลิสงโดยการสร้างแบบจำลองอุปทานและอุปสงค์ของตลาดเมล็ดถั่วลิสงในลักษณะระบบสมการเกี่ยวพัน รวมถึงการวิเคราะห์ผลกระทบต่อสวัสดิการของผู้ผลิต ผู้บริโภค และสังคม ภายใต้โครงสร้างดุลยภาพบางส่วนตามสถานการณ์ต่างๆ ของจำลองอุปสงค์การส่งออก ผลการศึกษาชี้ให้เห็นว่าการเปิดการค้าเสรีถั่วลิสงจะทำให้สวัสดิการของเกษตรกรเพิ่มขึ้นมากกว่าสวัสดิการของผู้บริโภคที่จะลดลงทั้งในด้านการบริโภคโดยตรงในรูปเมล็ดงาและน้ำมัน จะเป็นผลให้การเปลี่ยนแปลงสวัสดิการสุทธิทางสังคมดีขึ้น คำสำคัญ : ถั่วลิสง, ระบบสมการเกี่ยวพัน, ดุลยภาพบางส่วน, สวัสดิการ Abstract Abstract Groundnut has been enjoying a larger share in the domestic oilseed market and assuming a significant role in the livelihood of farmers and processors as well as consumers. However, oilseeds and oilseed product markets in Myanmar have been distorted by the government’s trade and agricultural policies. In order to achieve self-sufficiency in edible oil, groundnut seed export has been frequently banned even though the commodity has price competitiveness in the international market. Opening the market for groundnut would benefit the growers and processors under the multimarket aspects of this commodity. This study examines the impacts of trade liberalization of groundnut by constructing the supply and demand of groundnut seed market using simultaneous equations system. The partial equilibrium framework describes the welfare impacts on producers, consumers and society by measuring alternative scenarios of export demand. The results show that welfare gains of farmers are larger than the consumer surplus losses in both direct consumption and crushing sectors and consequently leading to a net gain for society. Keywords : groundnut, simultaneous equations, partial equilibrium, welfare